The grass subfamily Pooideae: Cretaceous–Palaeocene origin and climate‐driven Cenozoic diversification. Issue 8 (21st May 2019) - Schubert, Marian; Marcussen, Thomas; Meseguer, Andrea S.; Fjellheim, Siri
Abstract : Aim: Frost is among the most dramatic stresses a plant can experience, and complex physiological adaptations are needed to endure long periods of sub‐zero temperatures. Owing to the need to evolve these complex adaptations, transitioning from tropical to temperate climates is regarded as difficult. Here, we study the transition from tropical to temperate climates in the grass subfamily Pooideae, which dominates cool temperate, continental and Arctic regions. We produce a dated phylogeny and investigate the role of climate cooling in diversification. Location: Global, temperate regions. Time period: Cretaceous–Cenozoic. Major taxa: Pooideae. Methods: Using newly available fossils and methods, we dated a comprehensive Pooideae phylogeny and tested for the impact of palaeoclimates on diversification rates. Using ancestral state reconstruction, we investigated whether Pooideae ancestors experienced frost and winter. To locate the ancestral distribution area of Pooideae, we performed biogeographical analyses. Results: We estimated a Late Cretaceous/early Palaeocene origin of the Pooideae (61–77 Ma), with all major clades already having diversified at the Eocene–Oligocene climate cooling (34 Ma). Climate cooling was a probable driving force of Pooideae diversification. Pooideae probably evolved in a temperate niche experiencing frost, but not long winters. Main conclusion: Pooideae probably originated in a temperate niche and experienced cold temperatures and frost long before expansion of temperate biomes after the Eocene–Oligocene transition. This suggests that the Pooideae ancestor had adaptations to temperate climate and that certain responses to low‐temperature stress are shared in extant Pooideae grasses. Throughout the Cenozoic, falling temperatures and expansion of temperate biomes were associated with an increase in diversification. However, complex mechanisms for enduring strongly seasonal climate with long, cold winters most probably evolved independently in daughter lineages. Our findings provide insight into how adaptations to historical changes in chill and frost exposure influence the distribution of plant diversity today.